Solid-solid Phase Transitions between Crystalline Polymorphs of Organic Materials - Rietveld, Ivo B. (Current Pharmaceutical Design, 2023)
In this review, the analysis of solid-solid phase transitions between crystalline polymorphs of organic molecules is discussed. Although active pharmaceutical ingredients (APIs) are the scope of the review, whether an organic molecule has a biological activity or not does not particularly define its interactions in the crystalline state. Therefore, other small organic molecules have been included in this analysis and in certain cases, polymers have been discussed too. The focus of the review is on experimental analysis; however, a section on computational and theoretical methods has been added because these methods are becoming important and are obviously helpful in understanding for example transition mechanisms because the results can be easily visualized. The following aspects of solid-solid phase transitions between crystalline structures are presented in this review. The thermodynamics of phase transitions between polymorphs involving thermodynamic equilibrium and the variables temperature and pressure closely linked to the Gibbs free energy are discussed. The two main transition mechanisms in the organic crystalline solid, displacive and concerted, are discussed. Experimental methods that are used to understand the mechanisms and thermodynamic equilibrium between different polymorphs of an API are reviewed. The switching of polymorph properties is discussed, and heat storage and release are reviewed as it is one of the main applications of solid-state phase transitions. Of interest for the control of drug products, constraining phase transitions has been reviewed, as it may help increase the bioavailability of an API by using metastable phases. Finally, second order phase transitions of organic materials, which appear to be rare, are discussed. It can be concluded that although the general theory of polymorphism and phase transitions is well understood, how it works out for a specific molecule remains difficult to predict.
Keywords: crystal